Additive manufacturing of aluminium alloy 2024 by laser powder bed fusion: microstructural evolution, defects and mechanical properties. Issue 7 (19th July 2021) - Kumar, Manoj; Gibbons, Gregory J.; Das, Amitabha; Manna, Indranil; Tanner, David; Kotadia, Hiren R.
Abstract : Purpose: The purpose of this study is to investigate the microstructural evolution of high-strength 2024 Al alloy prepared by the laser powder bed fusion (L-PBF) additive manufacturing (AM) route. The high-strength wrought Al alloy has typically been unsuitable for AM due to its particular solidification characteristics such as hot cracking, porosity and columnar grain growth. Design/methodology/approach: In this research work, samples were fabricated using L-PBF under various laser energy densities by varying laser power and scan speed. The microstructural features that developed during the solidification are correlated with operating laser parameters. In addition, finite element modelling (FEM) was performed to understand the experimentally observed results. Findings: Microstructure evolution and defect formation have been assessed, quantified and correlated with operating laser parameters. Thermal behaviour of samples was predicted using FEM to support experimental observations. An optimised combination of intermediate laser power and scan speed produced the least defects. Higher energy density increased hot tearing along the columnar grain boundaries, while lower energy density promoted void formation. From the quantitative results, it is evident that with increasing energy density, both the top surface and side wall roughness initially reduced till a minimum and then increased. Hardness and compressive strength were found to decrease with increasing power density due to stress relaxation from hot tearing. Originality/value: This research work examined how L-PBF processing conditions influence the microstructure, defects, surface roughness and mechanical properties. The results indicates that complete elimination of solidification cracks can be only achieved by combining process optimisation and possible grain refining strategies.